A value-at-risk approach to banks' capital buffers: An application to the new Basel Accord - Esa Jokivuolle; Samu Peura (Bank of Finland, 2001)
The rating-sensitive capital charges on credit risks under the new Basel Accord are likely to increase the volatility of minimum capital requirements, which may force banks to hold larger capital cushions in excess of minimum requirements.We analyse this claim on the basis of numerical simulations on hypothetical bank portfolios, in which the bank's choice of capital cushion is assumed to satisfy a value-at-risk-type constraint.The results suggest that the size of the cushion depends on the bank's credit portfolio risk and its chosen approach for calculating the minimum capital requirement.Although the more ratings-sensitive internal ratings based approach imposes lower minimum capital requirements on sufficiently high-quality credit portfolios than does the standardised approach, this capital relief is countered by the need for larger relative cushions under the former approach.The results imply that the cushions induced by greater rating sensitivity may influence both banks' choices between proposed approaches for calculating capital requirements as well as the aggregate level of post-reform bank capital.Hence these cushions should be given due consideration in the final calibration of the Basel risk weights.
URN:NBN:fi:bof-20140807659
Keywords: 330; new Basel Capital Accord; credit risk; internal ratings; value-at-risk